ANALYSIS OF UNDERGRADUATE STUDENTS’ METACOGNITIVE AWARENESS BASED ON CLASS LEVEL - Kartika, Hendra; Firmansyah, Dani (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Metacognitive awareness is essential not only for school level learners, but also for higher level students. They are still experiencing the process of learning and the assumptions about what they learn still exist in their minds. Therefore it can lead to metacognitive awareness with different levels. However, metacognitive awareness based on class level is still yet to be explored. In this study, the level of undergraduate students’ metacognitive awareness according to class level was identified. The participants were 31 college mathematics education students per group from first, second, and third-years at a state university in Indonesia. The data were collected through the Metacognitive Awareness Inventory. The data were analyzed as numbers, mean scores and percentages on every participants. The findings showed that class level had no effect on level of students’ metacognitive awareness. It also indicated that although there are no students who have very low metacognitive awareness, but the higher the class level, the lower their average of metacognitive awareness. These findings suggest that there should be attention from teachers as well as efforts to enhance students’ metacognitive awareness.